HUBUNGAN MENTORING DENGAN KEBERHASILAN MAHASISWA EKONOMI SYARIAH PADA MATA KULIAH AKUNTANSI - FARIDAH, ROHANA; MUBARAK, ZAKI (Islamic Economics and Business Faculty of UIN Antasari, 2014)
The purpose of this research is to find out how affective a mentoring program that washeld by Islamic Economics Departement, Sharia and Islamic Economics Faculty and to find out therelationship between result of mentoring program and accounting subject. The methodology that isused in this research is quantitative with Wicoxon Test and Spearman Correlation Analysis. This studyshows that mentoring program in accounting subject which was given to the student at secondsemester doing effectively. Spearman Correlation Analysis shows that the student get a great point inboth mentoring program and accounting subject.